Antibiotic prophylaxis for patients with newly diagnosed multiple myeloma: Systematic review and meta‐analysis. (22nd February 2020) - Mohyuddin, Ghulam Rehman; Aziz, Muhammad; McClune, Brian; Abdallah, Al‐Ola; Qazilbash, Muzaffar
Abstract: Objective: Ascertain the benefit of prophylactic antibiotics for patients with newly diagnosed multiple myeloma (MM), given that clinical trials evaluating this have had conflicting results. Methods: We performed a systematic review and meta‐analysis evaluating the use of prophylactic antibiotics in patients with MM and its impact on infection risk and mortality. Results: Across three included studies, a total of 664 patients received antibiotics and 650 patients received no antibiotics. The overall incidence of infection within 3 months was lower for antibiotic group compared to placebo (18.4% vs 23.4%, RR: 0.79, 95% CI 0.62‐1.00, P = .05, I 2 = 6.5%). There was no difference in mortality in the first 3 months (1.5% vs 3.5%, RR: 0.47, 95% CI 0.17‐1.27, P = .60, I 2 = 28.1%). Conclusion: Antibiotic prophylaxis for a finite duration can decrease the overall incidence of infection within the first 3 months following diagnosis. This does not lead to a decrease in mortality. Further data on antibiotic resistance patterns, toxicity, healthcare expenditures, and the impact of antibiotics on subsequent therapies can assist providers in helping make decisions on prophylactic antibiotics with their patients.